Home Healthcare and the Medicare Fraud Strike Force. (November 2017) - Clark, Kyle; George, Andrew
Abstract : Modern federal healthcare fraud investigations use big data to find outliers among providers who are then targeted for enforcement actions. This approach is being used to pursue an outsized number of criminal cases against home healthcare agencies, resulting in decades-long prison sentences and tens of millions in fines. But it is remarkably transparent, giving home healthcare providers ample opportunity to stay out of harm's way. The government has provided the statistical characteristics by which it searches for fraud among home healthcare agencies, along with the benchmarks it uses to determine who is an outlier. And enforcement actions against home healthcare agencies have consistently targeted the same conduct: payments to payment recruiters and physicians in return for referring patients who often do not need the services billed. This article provides practical advice on how home healthcare agencies can gauge and limit their own legal exposure by monitoring their statistics against the government's benchmarks and by instituting basic controls to prevent targeted conduct.